Gender Inequality and its Implication for Inclusive Growth in Nigeria from 1980 to 2018 - Lawanson, Olukemi I; Umar, Dominic I (Asian Economic and Financial Review, 2019)
Earlier empirical studies on inequality concentrated more on its effects on economic growth with limited attention on its consequences for inclusive growth. Nigeria on average has achieved its annual target growth rate. However, stark realities of inequality, unemployment and poverty amid growth point to the need for inclusive growth. This paper examined the gender inequality implications for inclusive growth in Nigeria from 1980 to 2018 using data from the World Development Indicators (2018), National Bureau of Statistics (2018) and CBN Statistical Bulletin (2018).This study used the ARDL cointegration method in the analysis and the results showed that gender inequality in education and employment both in the short and in the long term portend grave consequences for inclusive growth in Nigeria. Government should take appropriate policy measures by ensuring equal access to education and employment for both men and women to minimize economic losses. Attaining inclusive growth in Nigeria is unlikely without gender equality. Therefore, this paper recommends that gender equality should be included in the National Development Agenda and be backed by policies that will enforce its operation both in public and private sectors at the local, state and federal government levels.